1990
DOI: 10.1128/jb.172.4.1814-1822.1990
|View full text |Cite
|
Sign up to set email alerts
|

A chromosomal Agrobacterium tumefaciens gene required for effective plant signal transduction

Abstract: The vir gene products of Agrobactenium tumefaciens carry out the transfer of T-DNA to the plant genome. Effective transcriptional induction of the vir genes by plant signal molecules is controlled by two vir gene products, VirA and VirG. In this study we have identified and cloned a chromosomal region which is also required for vir gene induction. Transposon insertions within this region reduce induction significantly and strongly attenuate virulence, resulting in a restricted host range for infection. The red… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

2
81
0

Year Published

1990
1990
2006
2006

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 114 publications
(83 citation statements)
references
References 51 publications
(43 reference statements)
2
81
0
Order By: Relevance
“…Putative chvE mutants were characterized by examining their ability to be complemented for pathogenicity on tomato plants by a strategy already developed for virA and virG mutants (see above). The clones used in this complementation analysis contained the chromosomal chvE region from strain C58, either intact in pMWH146 or with chvE inactivated by a transposon insertion in pMWH102 (11).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Putative chvE mutants were characterized by examining their ability to be complemented for pathogenicity on tomato plants by a strategy already developed for virA and virG mutants (see above). The clones used in this complementation analysis contained the chromosomal chvE region from strain C58, either intact in pMWH146 or with chvE inactivated by a transposon insertion in pMWH102 (11).…”
Section: Methodsmentioning
confidence: 99%
“…Conceivably, nonpathogenic mutants produced by A. tumefaciens in association with the host plant could be altered either in the vir or T region of the Ti plasmid or in the chromosome. Chromosomal genes that are required for efficient plant transformation include chvE, which encodes a protein that potentiates the effect of plant phenolic compounds on vir gene induction (11).…”
mentioning
confidence: 99%
“…Wild-type A. tumefaciens strain A723 (C58 chromosome, pTiB6806) and its derivatives A1059 (chvE::TnS), A1068 (chvE::TnS), and A1030 (virA::TnS) have been described (12,15). Wild-type strain A348 (C58 chromosome, pTiA6NC) (16) and its derivatives A348-MX1 (chvE::TnS) (12) and A348-MX226 (virA::Tn3-HoHol) (17) were substituted for A723 and its derivatives when indicated.…”
Section: Methodsmentioning
confidence: 99%
“…Sequence analysis of chvE showed that it codes for a protein of at least 31.5 kDa that is homologous to the periplasmic ribose-binding protein and galactose/glucosebinding protein (GBP) of Escherichia coli (12). Upon binding their respective sugars, these proteins in E. coli interact with separate sites in the periplasmic domain of the methylaccepting transmembrane signal protein Trg, resulting in chemotaxis toward the sugars.…”
mentioning
confidence: 99%
See 1 more Smart Citation